Fasting salivary pepsin level as a reliable non-invasive method of screening for laryngopharyngeal reflux in Egyptian patients - Manal Sabry; Tarek Mohamed Yosef; Ahmed Mohammed Mahmoud; Tari M. A. George Michael (SpringerOpen, 2022)
Abstract Background Laryngopharyngeal reflux (LPR) is caused by the regurgitation of gastric contents above the upper esophageal sphincter. Diagnostic gold standard tests like multichannel intraluminal impedance (MII) and 24-h dual-probe pH-metry are invasive and expensive which limits their accessibility especially in resource-limited settings. Since pepsin is only produced in the stomach, detecting pepsin in the laryngopharynx would make it a specific marker for reflux. Therefore, in this study, we measured fasting salivary pepsin in patients with symptoms suggestive of LPR. We aimed to confirm the role of fasting salivary pepsin as a non-invasive diagnostic tool of LPR, to detect a cut-off value for it in Egyptian patients and to study predictors of changes in its level. Methods We conducted a prospective case control study at the gastroenterology clinic in Ain Shams University Hospitals. After testing with esophageal pH-metry, 25 symptomatic patients with confirmed LPR and 25 healthy controls were enrolled in the study. Patients diagnosed with organic upper gastrointestinal disorders, autoimmune diseases, diabetes, malignancy or organ failure were excluded. Patients on PPI were advised to stop 2 weeks before testing. All patients were tested for fasting salivary pepsin levels, esophageal pH-metry, and indirect laryngoscopy in addition to routine laboratory parameters. Results Out of the 25 LPR patients, 16% of patients had laryngoscope abnormality in the form of mucosal hyperemia and inflammation, and the average percentage of time pH < 4 in esophageal pH-metry testing was 29.14 ± 39.5%. Comparative study between the 2 groups revealed a significant increase in salivary pepsin in LPR group compared to control group (p < 0.001). By using ROC-curve analysis, salivary pepsin at a cut-off point > 5 ng/ml diagnosed patients with LPR, with fair (77.9%) accuracy, sensitivity = 100% and specificity = 56% (p = 0.0001) while pH-metry (% Time pH < 4) at a cut-off point > 14% diagnosed patients with LPR, with good (87%) accuracy, sensitivity = 80%, and specificity = 100% (p < 0.0001) Conclusion Fasting salivary pepsin level at a cut-off value of > 5 ng/ml is a reliable, non-invasive method for detection of LPR especially in resource-limited settings.